Trauma, the body and transformation : a narrative inquiry - Etherington, Kim (Jessica Kingsley Publishers, 2003)
Trauma suffered during childhood can affect not only a person's emotional and mental health, but also their physical health, even into adulthood. This unique book fills a gap in research in this area, providing personal and theoretical perspectives on trauma and recovery. The contributors tell powerful stories of traumatic childhood events, including bereavement, abuse and evacuation and separation from parents. They document their reactions to trauma whether through illness, disability, addiction, psychosomatic disorders, self-harming behaviours or dissociation. Each author also shows the pat.